2022
DOI: 10.1007/s10072-022-05956-6
|View full text |Cite
|
Sign up to set email alerts
|

Are COVID-19 vaccines safe for people with epilepsy? A cross-sectional study

Abstract: Background COVID-19 disease was first seen in December 2019 and was declared a pandemic soon after. To fight the pandemic, there is an immense need for effective vaccines. The purposes of our study were to investigate the effect of coronavirus vaccines on seizures in people with epilepsy (PWE) and assess the adverse events of COVID-19 vaccine in PWE. Methods This was a cross-sectional study. We included epilepsy patients who got vaccinated with two or three doses at least 1 month earlier. We gathered the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 21 publications
8
49
2
Order By: Relevance
“…After screening 82 duplicates and 152 papers through titles and abstracts, we retrieved the full texts of the remaining 16 studies. Ten observational studies and two case reports studies [17] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] that met the inclusion criteria were included in this systematic review and meta-analysis ( Figure 1 ).
Figure 1 Flow diagram of study
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening 82 duplicates and 152 papers through titles and abstracts, we retrieved the full texts of the remaining 16 studies. Ten observational studies and two case reports studies [17] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] that met the inclusion criteria were included in this systematic review and meta-analysis ( Figure 1 ).
Figure 1 Flow diagram of study
…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [17] , [23] , [24] , [25] , [26] , [29] , [30] provided the information of primary outcome (vaccination status), and six studies [22] , [24] , [25] , [26] , [28] , [29] reported the secondary outcomes of vaccination willingness and unwillingness. Seven studies [17] , [23] , [24] , [25] , [26] , [27] , [30] reported the incidence of adverse effects after COVID-19 vaccination. Supplemental Table 1 summarizes the inclusion, exclusion criteria and definition of seizure free in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, only a few studies addressed the relationship between PWE and SARS-CoV-2 vaccination [17] , [18] , [19] , [20] . These studies aimed to explore the safety and tolerability of vaccination among PWE, as well as the vaccination rates and the reasons for refusing.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, these studies were based on questionnaires completed by the patients, associating an inevitable selection bias. The first studies [18] , [19] , [20] included small and poorly extrapolable samples. In addition, vaccination rates were relatively low at the time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation